X-ray powder diffraction analysis of a silver(I)-aspartame complex - Putvinskis, R.; Paiva-Santos, C. O.; Cavicchioli, M.; Massabni, Antonio Carlos [UNESP] (J C P D S-int Centre Diffraction Data, 2006)
Synchrotron X-ray powder diffraction (XRPD) data were collected for the silver(I)-aspartame complex [Ag(C14H17N2O5)]center dot 1/2 H2O. The complex was obtained from a stoichiometric mixture of aspartame (3-amino-N-(alpha-carboxyphenethyl)-succinamic acid N-methyl ester, C14H18N2O5), Na2CO3, and AgNO3. Indexing using Crysfire and Chekcell proposed an orthorhombic unit cell with space group P222(1). The lattice parameters are a = 12.4750(1) angstrom, b = 21.60614(14) angstrom, and c = 4.88888(9) angstrom. (C) 2006 International Centre for Diffraction Data.
Keywords: silver(I)-aspartame; X-ray diffraction; Le Bail method